A comparative study of the attitude of the constitutions of the Islamic Republic of Iran and Pakistan to children's rights - Mohammad javad Hosseini; Hassan Khosravi (مطالعات تطبیقی حقوق کشورهای اسلامی)
Respecting the rights of the child is of particular importance due to physical and mental weakness and the lack of development of intelligence and intelligence, because the future human being is formed in childhood, and whatever is experienced in childhood becomes effective and shapes the person's personality in adulthood. With the expansion of human rights in many legal systems, the basic laws have taken on the appearance of more human rights and each of them has expressed the guarantees of citizens' rights in some way. In this article, the position of children's rights in the two constitutions of the Islamic Republic of Iran and Pakistan and some declarations and international conventions have been compared in a descriptive and analytical way. The purpose of this article is to measure the observance of children's rights in the legal system of these two Islamic and Republic countries. Despite the acceptance of the Convention on the Rights of the Child and the obligation to respect the rights of the child in all its manifestations, these two constitutions did not state all the standards related to the rights of the child and later they did not revise their constitution to include these principles and only some of the principles Such as the right to have freedom of opinion and expression, the right to education and training, special childhood care and compliance with work standards have been guaranteed and positive discriminations have been considered for children.